IOT Implementation Energy consumption for Indoor Orchid Cultivation based on WeMos - anton breva yunanda (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
Orchids are epiphytic plants with high popularity. Orchid is a plant that can process its own nutrients with the help of other media. Parameters that need to be monitored include air temperature, air humidity, and soil moisture. These parameters greatly affect plant growth. Plants can grow well if humidity, temperature, and light intensity are met properly. Good orchid humidity ranges from 50 – 80%. Humidity should not be too high at night and not too low during the day. In addition to humidity, the temperature where you plant orchids must also be maintained. The ideal temperature for orchids is daytime temperatures between 27-30 degrees Celsius and night temperatures between 21-24 degrees Celsius. Based on these problems, a Design and Development Tool for Monitoring Soil Temperature and Moisture on the Growth of Indoor Orchid Plants is Based on WeMos with Indoor Energy. In this design, the results of sensor readings will be displayed in the form of data which will be accessed via the web server on WeMos. To read the temperature, air humidity, and soil moisture, several sensors are used, namely: DHT 22, soil moisture sensor, and a relay connected to a mini water pump using an indoor cultivation method where the energy source uses UV waves by LED light. From the results of the implementation and testing, the growth period will be obtained more faster than the normal cultivation. hopefully, this research will help people who care for orchid plants to be able to monitor their orchid plants efficiently in indoor conditions so that these orchid plants can always be in the best conditions of temperature, light, and soil moisture.